Sociodemographic factors of violent deaths related to licit or ilicit psychoactive substances: a cross-sectional study, Ceará, Brazil, 2015-2019 - Wanderley Pinheiro de Holanda Júnior; Raimunda Hermelinda Maia Maceno; Maria Augusta Drago Ferreira (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To assess association between sociodemographic factors, presence of licit or illicit psychoactive substances, and types of legal death in Ceará state, Brazil. Methods Cross-sectional study based on autopsy data and toxicology tests on victims of cases registered by the Ceará Forensic Expert service, from 2015 to 2019. Results Of the 4,198 cases analyzed, 55.6% were positive for licit and/or illicit substances, with greater frequency of benzodiazepines (22.4%) and cocaine (21.7%) among males (45.0%), young adults (58.7%), single people (49.0%), and those with low education levels (52.8%). Association was found between benzodiazepines (29.5%) and tricyclic antidepressants (15.6%) and suicides; cocaine (28.1%) and cannabis (27.1%) and homicides; and cocaine (28.2%) and tricyclic antidepressants (5.9%) and suspicious deaths. Conclusion Sociodemographic factors were associated with the use of psychoactive substances and types of legal death. Benzodiazepines and cocaine were the most frequent substances in suicide and homicide cases, respectively.